2016
DOI: 10.1111/crj.12561
|View full text |Cite
|
Sign up to set email alerts
|

Allergic rhinitis, rhinoconjunctivitis, and eczema: prevalence and associated factors in children

Abstract: Allergic conditions like allergic rhinitis, rhinoconjunctivitis, and eczema are prevalent among Indian children and are associated with environmental tobacco smoke, paracetamol use, antibiotic use, television watching, and outdoor and indoor air pollution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
85
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 26 publications
3
85
0
7
Order By: Relevance
“…7 Several studies suggested that seasonal climate changes might lead to the seasonal variation of prevalence and clinical features in eczema. asthma), [14][15][16][17] very few researches have examined the influence of air pollution on eczema. 10 However, recent studies have not adequate evidence for the association between eczema and environmental factors while our knowledge regarding the effects of air pollutants on skin health is limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Several studies suggested that seasonal climate changes might lead to the seasonal variation of prevalence and clinical features in eczema. asthma), [14][15][16][17] very few researches have examined the influence of air pollution on eczema. 10 However, recent studies have not adequate evidence for the association between eczema and environmental factors while our knowledge regarding the effects of air pollutants on skin health is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Although many researches have reported air pollution aggravated numerous human diseases, including raising morbidity and mortality from cardiopulmonary diseases [11][12][13] and some allergic diseases (e.g. asthma), [14][15][16][17] very few researches have examined the influence of air pollution on eczema. Several studies indicate that exposure to air pollutants increases the risk of eczema in childhood or exacerbates atopic eczema symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…According to the latest studies, the increase in the prevalence of allergic diseases has plateaued in developed countries, but is still continuing in developing countries [5,6]. However, studies that evaluate the change in the prevalence of allergic diseases in the long term are limited within the literature [6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The phase 3 International Study of Asthma and Allergy in Children (ISAAC) 1 reported an overall prevalence of current wheeze of 7% in Indian children aged 6-7 years and aged 13-14 years, with a higher prevalence of up to 10-20% in some areas. 2 Importantly, 50% or more of this cohort had severe uncontrolled asthma. 1 An Indian study reported that prevalence of allergic rhinitis was 11·3% in children aged 6-7 years, and 24·4% in children aged 13-14 years.…”
Section: The Burden Of Allergic Diseases In the Indian Subcontinent: mentioning
confidence: 91%
“…1 An Indian study reported that prevalence of allergic rhinitis was 11·3% in children aged 6-7 years, and 24·4% in children aged 13-14 years. 2 The ISAAC study 4 reported 2·7% overall prevalence of current eczema among Indian children aged 6-7 years, and 3·6% among Indian children aged 13-14 years. In contrast to the high prevalence of rhinitis, asthma, and eczema, food allergy was low at 0·14% among Indian children aged 6-11 years.…”
Section: The Burden Of Allergic Diseases In the Indian Subcontinent: mentioning
confidence: 99%